Analisis Peningkatan Kinerja Karyawan melalui Motivasi Kerja Internal dan Motivasi Eksternal Karyawan - Hairudin Hairudin; Eka Travilta Oktaria (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to analyze internal work motivation and external work motivation on employee performance at PT. Fontera Brand Indonesia Bandar Lampung Branch. Method: The research method used in this study is a quantitative method with a census approach. Data collection techniques based on data sources in this study uses a questionnaire method. The analysis technique used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation analysis and coefficient of determination, F test, and t test. Result: Work motivation both internally and externally simultaneously has a significant effect on employee performance at PT. Fontera Brand Indonesia Bandar Lampung Branch; Partial internal work motivation has a significant effect on employee performance at PT. Fontera Brand Indonesia Bandar Lampung Branch; External work motivation partially has a significant effect on employee performance at PT. Fontera Brand Indonesia Bandar Lampung Branch. Limitation: This study only assesses the variables of internal and external motivation and the performance of employees working at PT. Fontera Brand Indonesia Bandar Lampung Branch, as well as clear literacy limitations on employee motivation. Contribution: This research provides suggestions for PT. Fontera Brand Indonesia Bandar Lampung Branch to provide performance motivation both internally and externally for employees who can provide output in terms of improving employee performance so that it is more leverage. Novelty: The novelty in this study lies in the conditions carried out by researchers during the transition from pandemic to endemic, so that they pay attention to differences in research results with previous studies that have been conducted.